2015
DOI: 10.1126/scisignal.aaa4312
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of brain glutamate metabolism by nitric oxide and S-nitrosylation

Abstract: Nitric oxide (NO) is a signaling intermediate during glutamatergic neurotransmission in the central nervous system (CNS). NO signaling is in part accomplished through cysteine S-nitrosylation, a posttranslational modification by which NO regulates protein function and signaling. In our investigation of the protein targets and functional impact of S-nitrosylation in the CNS under physiological conditions, we identified 269 S-nitrosocysteine residues in 136 proteins in the wild-type mouse brain. The number of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 87 publications
(150 reference statements)
2
81
0
Order By: Relevance
“…Accordingly, VLCAD is S-nitrosylated under basal conditions with low levels of NO, i.e., in the absence of cell stress or disease. Additionally, this same group of Harry Ischiropoulos found that several enzymes involved in glutamate metabolism are S-nitrosylated under basal conditions in mouse brain [48]. One such enzyme, glutamate dehydrogenase (GDH) oxidizes glutamate to α-ketoglutarate, which can feed into the TCA cycle.…”
Section: Tca Cycle Enzymes As Targets Of S-nitrosylationmentioning
confidence: 99%
“…Accordingly, VLCAD is S-nitrosylated under basal conditions with low levels of NO, i.e., in the absence of cell stress or disease. Additionally, this same group of Harry Ischiropoulos found that several enzymes involved in glutamate metabolism are S-nitrosylated under basal conditions in mouse brain [48]. One such enzyme, glutamate dehydrogenase (GDH) oxidizes glutamate to α-ketoglutarate, which can feed into the TCA cycle.…”
Section: Tca Cycle Enzymes As Targets Of S-nitrosylationmentioning
confidence: 99%
“…Using these approaches, over 300 endogenous S-nitrosylation sites on ϳ200 proteins were identified from mouse liver (63). Ischiropoulos and colleagues further utilized this phenylmercury-based SNO-capture approach to identify up to 1,000 S-nitrosylation sites on hundreds of proteins in various mouse tissues (64,65). The number of S-nitrosylation sites in vivo to nitric oxide were found to be substantially dependent on endothelial nitric oxide synthase (eNOS) or neuronal nitric oxide synthase (nNOS) (64,65).…”
Section: The Expanding Landscape Of the Thiol Redox Proteomementioning
confidence: 99%
“…3A); these residues may be required for base-catalyzed transnitrosation (1,46). To test the robustness of the motif, we performed pLOGO analysis using an independently published SNO-proteome from brains of wild-type (C57BL/6J) mice (47) and found an enrichment of the basic residues-Lys (K), Arg (R), and His (H)-surrounding the SNO-Cys position (Fig. S2C, -6, -5, -1, +3, and +4).…”
Section: S1mentioning
confidence: 99%